2020
DOI: 10.1021/acsomega.0c04938
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Janus Transition Metal Dichalcogenide Monolayers for Acetone Gas Sensing

Abstract: Recently, Janus two-dimensional (2D) transition metal dichalcogenides (TMDs) have been widely investigated and have provided exciting prospects in many fields such as photoelectric materials, photocatalysis, and gas sensors. In this study, we performed density functional theory (DFT) calculations to study the sensitivity of four volatile organic compounds (VOCs), including acetone, methanol, ethanol, and formyl aldehyde, over pristine 2D TMDs and 2D Janus TMD monolayers. We found that MoS 2 , Janus MoSSe, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 67 publications
(92 reference statements)
0
31
0
Order By: Relevance
“…Janus TMDs materials have distinct properties such as asymmetric crystal structure, intrinsic out-ofplane polarization, and piezoelectricity. [18][19][20][21][22][23] The 2D/2D van der Waals heterostructures coupling is important, it produces a variety of interesting effects 24,25 it is a useful method for combining various properties from 2D different materials 26 to promote PV technology innovation. 27 By stacking the two monolayers together, the MXO/MoX 2 heterostructure can be constructed based on this advantage and tunable properties.…”
Section: Introductionmentioning
confidence: 99%
“…Janus TMDs materials have distinct properties such as asymmetric crystal structure, intrinsic out-ofplane polarization, and piezoelectricity. [18][19][20][21][22][23] The 2D/2D van der Waals heterostructures coupling is important, it produces a variety of interesting effects 24,25 it is a useful method for combining various properties from 2D different materials 26 to promote PV technology innovation. 27 By stacking the two monolayers together, the MXO/MoX 2 heterostructure can be constructed based on this advantage and tunable properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one of the most significant magnetization methods is doping the material with transition elements of different periods of the periodic table. Some of the works performed in this area are noted in the following [16][17][18][19][20][21][22][23][24][25][26][27][28] . Octa et al 17 created the T and H-phase conditions on an extensive range of TMCs and investigated the magnetization conditions on the structures.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the works performed in this area are noted in the following [16][17][18][19][20][21][22][23][24][25][26][27][28] . Octa et al 17 created the T and H-phase conditions on an extensive range of TMCs and investigated the magnetization conditions on the structures. They revealed that VX2 (where X could be O, S, Se, or Te) is magnetized at each of the two phases, while NiX2 is not.…”
Section: Introductionmentioning
confidence: 99%
“…For example, using rst-principle calculations, Janus MoSSe monolayers have been studied in the sensing NO 2 , NH 3 , SOF 6 decompositions species, adulterant compounds, and volatile organic compounds (VOCs). [22][23][24][25][26][27][28] In these reports, the sensing properties depend on electronic interactions and adsorption strength between the target gaseous molecules and the sensor materials. The enormous adsorption energy will lead to stronger sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have investigated that acetone possesses a good sensitivity over the Janus MoSSe monolayer. 26 Besides, it has been reported that external electric fields show high reactivity to polar gas molecules during their adsorption. Since acetone is a well-known polar gas molecule, we will study the adsorption of acetone on both Janus MoSSe and pristine MoS 2 monolayers under external electric fields.…”
Section: Introductionmentioning
confidence: 99%